Estimating spatiotemporal availability of transboundary fishes to fishery‐independent surveys. Issue 10 (23rd July 2021) - O'Leary, Cecilia A.; Kotwicki, Stan; Hoff, Gerald R.; Thorson, James T.; Kulik, Vladimir V.; Ianelli, James N.; Lauth, Robert R.; Nichol, Daniel G.; Conner, Jason; Punt, André E.
Abstract: Taxa can expand beyond historical scientific survey footprints and into new areas with different survey protocols as they move to track their preferred climate. In global groundfish fisheries, for example, scientists estimate population dynamics within the spatial extent of a fishery‐independent survey using an index known as a design‐based estimator. Observed changes in species distribution in recent years suggest that some groundfish are moving beyond the spatial extent of single surveys. We must intercalibrate disparate data that cover a larger spatial extent to maintain our ability to accurately index populations as their availability to historical surveys changes. We combine US and Russian data from the northern, eastern and western Bering Sea to understand the proportion of fish biomass within the extent of the eastern survey ('availability'). Surveys are within close proximity to each other, but with different sampling protocols (hence catch a different proportion of local densities, termed 'sampling efficiency ratio'). We use Alaska pollock Gadus chalcogrammus, Pacific cod Gadus macrocephalus and Alaska plaice Pleuronectes quadrituberculatus as case studies to calculate survey efficiency ratios and two area‐swept estimators, termed local and conventional, to summarize groundfish biomass over various spatial scales across the Bering Sea. We estimated variation in spatial availability of transboundary stocks to the eastern Bering Sea (EBS) survey. In 2017, the most recent available year of survey coverage that included all three Bering Sea regions, estimated availability in the EBS of pollock biomass was ~33%, cod biomass was ~27% and plaice biomass was ~26%, down from ~58%, ~71% and ~30%, respectively, in 2010. Synthesis and applications . This is the first study to provide an empirical way to combine Russian and US data in the Bering Sea to assess changes in the availability of groundfish biomass, which, in turn, will alter the interpretations and values of population indices used in regional management. We recommend leveraging this approach using existing global fishery‐independent datasets that span different spatiotemporal footprints to monitor transboundary stocks, and as a template to initiate international cooperation on the assessment of spatial availability of stocks common to multiple countries. Abstract : This is the first study to provide an empirical way to combine Russian and US data in the Bering Sea to assess changes in the availability of groundfish biomass, which, in turn, will alter the interpretations and values of population indices used in regional management. We recommend leveraging this approach using existing global fishery‐independent datasets that span different spatiotemporal footprints to monitor transboundary stocks, and as a template to initiate international cooperation on the assessment of spatial availability of stocks common to multiple countries.